Inhibitory effect of isomaltodextrin on tyrosine metabolite production in rat gut microbiota. Issue 4 (2nd April 2020) - Takagaki, Ryodai; Yoshizane, Chiyo; Ishida, Yuki; Sakurai, Takeo; Taniguchi, Yoshifumi; Watanabe, Hikaru; Mitsuzumi, Hitoshi; Ushio, Shimpei; Morita, Hidetoshi
ABSTRACT: We examined the effect of isomaltodextrin (IMD), a soluble dietary fiber, on production of putrefactive products by intestinal bacteria using a tyrosine load test to measure phenol production in IMD-treated rats. We observed a significant increase in phenol and p-cresol concentrations in rats administered with only tyrosine, but not for rats co-administered tyrosine and IMD. To elucidate the mechanism of this effect, we analyzed the intestinal microbiota in each group and found that although IMD had no direct effect on the proportion of bacteria known to produce phenols, it did alter the balance of intestinal microbiota. The results suggested that changes in the intestinal microbiota composition reduced the metabolic capacity for tyrosine and in turn suppressed production of phenol or p-cresol, putrefactive products in the intestine. Graphical abstract: : Isomaltodextrin inhibits the phenols production of gut microbiota by reducing pH.